Integrating Arabic Football Commentary into Arabic Learning : A Stylistic-Pedagogical Model - Segaf Baharun; Hanifansyah, Nur (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
This study investigates the potential of Arabic football commentary as an authentic pedagogical tool to enhance learners’ stylistic competence in Arabic. Traditional teaching methods often emphasize memorization, which limits spontaneous and expressive use of language. To address this gap, the research aims to explore how football commentary can foster learners’ awareness and application of Arabic stylistic expression. Using a qualitative pedagogical case study, data were collected from 30 undergraduate students of Arabic Language and Literature at Universitas Islam Internasional Darullughah Wadda’wah. The research process consisted of three stages: analysis of professional commentators’ rhetorical features, practice sessions where participants produced their own commentary, and focused group discussions to capture learners’ perceptions. Findings reveal that this method improved students’ sports-related vocabulary, rhetorical skills such as metaphor and hyperbole, and overall motivation. Challenges included the rapid pace of commentary and dialectal interference, which require structured instructor guidance. The novelty of this study lies in systematically integrating football commentary into language teaching, transforming a popular cultural practice into a structured pedagogical approach. It is suggested that Arabic curricula incorporate authentic commentary activities to enrich stylistic learning and inspire more engaging classroom practices.